THE EFFECT OF OVAPRIM INJECTIONS COMBINATION WITH OXYTOCIN ON OVULATION AND THE QUALITY OF EGG LELAN (Osteochilus pleurotaenia Blkr) - Hartati, Gusrita; Aryani, Netti; Nuraini, Nuraini (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACT This research was conducted on November-December 2020at Fish Hatchery and Breeding Laboratory of Fishery and Marine Science Faculty of Riau University. The purpose of this study was to determine the effect of combining different doses of ovaprim and oxytocin on the ovulation stimulation and the quality of egg Lelan and to know the best combination of ovaprim dose and oxytocin for ovulation and quality of egg Lelan. The Method used is an experimens method using a complete randomized design with four treatments and three repetitions. The treatments used was P0 (100% vaprim), P1 ((75% Ovaprim + (25% Oxytosin x Results 75% ovaprim)), P2 ((50% Ovaprim + (50% Oxytosinx Results 50% ovaprim)), and P3 ((25% Ovaprim + (75% Oxytosin x Results 25% ovaprim)). The results showed that giving ((50% Ovaprim + (50% Oxytosin x Results 50% ovaprim)) body weight gave the best result with the latent time obtained (7.12 hours), total eggs stripping (184 eggs/gr broodstock), value of ovisomaic index (11,75 %), eggs diameter increment (0,11mm), egg maturity increment(14,33 %) and fertilization (19,19 %). The water quality parameters with temperature 25-280C, pH 5-7 and dissolved oxygen 3,77-5,2 ppm.Keywords : Ovaprim dose, oxytocin dose, ovulation and egg quality, Osteochilus pleurotaenia Blkr